The effects of intraoperative lung protective ventilation with positive end-expiratory pressure on blood loss during hepatic resection surgery: A secondary analysis of data from a published randomised control trial (IMPROVE). Issue 4 (April 2016) - Neuschwander, Arthur; Futier, Emmanuel; Jaber, Samir; Pereira, Bruno; Eurin, Mathilde; Marret, Emmanuel; Szymkewicz, Olga; Beaussier, Marc; Paugam-Burtz, Catherine
Abstract : BACKGROUND: During high-risk abdominal surgery the use of a multi-faceted lung protective ventilation strategy composed of low tidal volumes, positive end-expiratory pressure (PEEP) and recruitment manoeuvres, has been shown to improve clinical outcomes. It has been speculated, however, that mechanical ventilation using PEEP might increase intraoperative bleeding during liver resection. OBJECTIVE: To study the impact of mechanical ventilation with PEEP on bleeding during hepatectomy. DESIGN: Post-hoc analysis of a randomised controlled trial. SETTING: Seven French university teaching hospitals from January 2011 to August 2012. PARTICIPANTS: Patients scheduled for liver resection surgery. INTERVENTION: In the Intraoperative Protective Ventilation trial, patients scheduled for major abdominal surgery were randomly assigned to mechanical ventilation using low tidal volume, PEEP between 6 and 8 cmH2 O and recruitment manoeuvres (lung protective ventilation strategy) or higher tidal volume, zero PEEP and no recruitment manoeuvres (non-protective ventilation strategy). MAIN OUTCOME AND MEASURE: The primary endpoint was intraoperative blood loss volume. RESULTS: A total of 79 (19.8%) patients underwent liver resections (41 in the lung protective and 38 in the non-protective group). The median (interquartile range) amount of intraoperative blood loss was 500 (200 to 800) ml and 275 (125 to 800) ml in the non-protective and lung protective ventilation groups, respectively ( P  = 0.47). Fourteen (35.0%) and eight (21.5%) patients were transfused in the non-protective and lung protective groups, respectively ( P  = 0.17), without a statistically significant difference in the median (interquartile range) number of red blood cells units transfused [2.5 (2 to 4) units and 3 (2 to 6) units in the two groups, respectively; P  = 0.54]. CONCLUSION: During hepatic surgery, mechanical ventilation using PEEP within a multi-faceted lung protective strategy was not associated with increased bleeding compared with non-protective ventilation using zero PEEP. TRIAL REGISTRATION: The current study was not registered. The original Intraoperative Protective Ventilation study was registered on clinicaltrials.gov; number NCT01282996.